Inactivation of nontuberculous mycobacteria by gaseous ozone treatment. Issue 6 (June 2023) - Misawa, Kana; Nishimura, Tomoyasu; Kashimura, Shoko; Hasegawa, Naoki
Abstract: Nontuberculous mycobacteria (NTM) are environmental bacteria resistant to many common disinfectants and ultraviolet radiation. Inhalation of aerosols generated from NTM-containing water and soil causes NTM lung disease, especially in people with underlying lung diseases and decreased immunity. To prevent healthcare-acquired NTM infections, it is important to eradicate NTM living in hospital environments. Therefore, we evaluated the efficacy of gaseous ozone for the inactivation of NTM, namely Mycobacterium ( M. ) avium, M. intracellulare, M. kansasii, M. abscessus subsp. abscessus and M. abscessus subsp. massiliense. Gaseous ozone treatment at 1 ppm for 3 h reduced the bacterial number of all strains by more than 97%. Gaseous ozone treatment could be a practical, effective and convenient disinfection method for NTM living in hospital environments.